Sistem Pendukung Keputusan Untuk Menentukan Bibit Sawit Unggul Menggunakan Metode Analytic Hierarchy Process (AHP) - Reka Rama Rani; Fajri Profesio Putra; Elvi Rahmi (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This research presents the development of a Decision Support System aimed at assisting in the enhancement of palm oil production using the Analytic Hierarchy Process (AHP) method. The rapid growth in the palm oil industry necessitates a scientific approach to selecting seedlings with optimal growth potential and yield. In this context, the application of artificial intelligence-based technology, such as decision support systems, is essential in the process of selecting superior palm oil seedlings. The objective of this study is to model the criteria for selecting the most superior palm oil seedlings using the Analytical Hierarchy Process (AHP) method by comparing three criteria: leaflet shape, seedling root shape, and prospective trunk size. The result of this process is a decision support system that displays the value range of each palm oil seedling variety, thus facilitating farmers in choosing the most superior seedlings.